Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep25145
|View full text |Cite
|
Sign up to set email alerts
|

Low protein diets produce divergent effects on energy balance

Abstract: Diets deficient in protein often increase food consumption, body weight and fat mass; however, the underlying mechanisms remain poorly understood. We compared the effects of diets varying in protein concentrations on energy balance in obesity-prone rats. We demonstrate that protein-free (0% protein calories) diets decreased energy intake and increased energy expenditure, very low protein (5% protein) diets increased energy intake and expenditure, whereas moderately low protein (10% protein) diets increased ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
102
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 62 publications
21
102
4
2
Order By: Relevance
“…The protein leverage theory postulates that protein intake is regulated in mammals such that protein‐deficient diets are overconsumed in an attempt to meet protein requirements, whereas protein‐rich diets decrease food intake to calibrate for protein needs . Consistent with this hypothesis, we and others have shown that protein‐deficient diets are hyperphagic and thermogenic, while protein‐rich diets are hypophagic in rodents . The responses to protein dilution are, in part, mimicked by dietary restriction of the amino acids methionine or leucine, which promote hyperphagia and thermogenesis , whereas dietary deprivation of essential amino acids causes anorexia and weight loss .…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…The protein leverage theory postulates that protein intake is regulated in mammals such that protein‐deficient diets are overconsumed in an attempt to meet protein requirements, whereas protein‐rich diets decrease food intake to calibrate for protein needs . Consistent with this hypothesis, we and others have shown that protein‐deficient diets are hyperphagic and thermogenic, while protein‐rich diets are hypophagic in rodents . The responses to protein dilution are, in part, mimicked by dietary restriction of the amino acids methionine or leucine, which promote hyperphagia and thermogenesis , whereas dietary deprivation of essential amino acids causes anorexia and weight loss .…”
Section: Introductionmentioning
confidence: 52%
“…Restrictions of dietary protein , methionine by 80% , or leucine by 85% were reported to promote hyperphagia and thermogenesis; however, little is known of whether restriction of other essential amino acids also produces similar responses. Our study revealed several important findings on the effects of tryptophan restriction on energy balance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This goes to support the fact that even lean people with less fat mass grower's mash specially prepared for the growth of poulets that are of commercial use. Diets deficient in protein often increase food consumption, body weight and fat mass [26][27][28][29][30]; however, the underlying mechanisms remain poorly understood of the underlying mechanisms by which moderate protein deficiency…”
Section: Discussionmentioning
confidence: 99%